UNDERSTANDING TRANSLATION THEORIES: BRIDGING CULTURES THROUGH LANGUAGE (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Translation, as a pivotal mechanism for intercultural communication, has long been the subject of extensive theoretical inquiry. This abstract provides a concise overview of key translation theories that have shaped the practice and study of translation in the English language. This abstract encapsulates the rich tapestry of translation theories, offering a glimpse into the diverse approaches and perspectives that inform the complex process of rendering meaning across languages and cultures. By understanding these theories, translators can navigate the multifaceted challenges of translation with greater insight and sensitivity, fostering meaningful cross-cultural communication and understanding.